Estudio de craneoplastía in situ empleando cemento de polimetilmetacrilato - Rodríguez Basili, Florencia; Bulacio, José; Merenzon, Martín; Latorre, Fernando; Seoane, Pablo; Seoane, Eduardo (Revista Argentina de Neurocirugía, 2024)
Background. Repairing bone defects remains a challenge in neurosurgical practice, especially when autologous bone replacement is not feasible. One of the most frequently used alloplastic materials is polymethylmethacrylate (PMMA), which allows for "in situ" modeling of the bone defect. Objectives. To describe cranioplasty with PMMA with “in situ” modeling and report the complications of a series of cases. Methods. A retrospective study was conducted on a series of patients operated on for cranial bone defects between 2017 and 2022, using a PMMA cement prosthesis with “in situ” modeling. Patients with a follow-up of more than 12 months were included. Demographic variables, clinical characteristics, and postoperative complications were analyzed. The Visual Analog Scale for Cosmetics Results (VASC) was used to assess patient satisfaction, and the Visual Analog Scale for Postoperative Pain (VASD) was used to evaluate postoperative pain. Results. Twenty patients were included, with an average age of 37.4 ± 16.7 years, and 55% (n=11) were female. Admission diagnoses included posterior fossa tumors (60%), post-traumatic cranial bone defects (20%), supratentorial tumors (10%), an orbital tumor (5%), and trigeminal neuralgia (5%). PMMA prostheses were used in all cases for bone defect reconstruction. The Visual Analog Scale for Cosmetics Results (VASC) indicated satisfactory results with the surgical procedure (average 8.6±1.1). Only one superficial wound complication was observed, without requiring further surgical intervention. Patients did not report postoperative pain. Conclusion. The use of PMMA prostheses with “in situ” modeling in our series represents a safe option with good cosmetic results, not associated with higher complication rates compared to those described for other materials.